Molecular and agro-morphological evaluations of interspecific hybridisation in two wild yams (Dioscorea spp.) for genetic improvement - Oyedoyin, F.P.; Olawuyi, O.J.; Agre, P.A.; Asfaw, A. (Elsevier, 2025)
Yam (Dioscorea spp.) is an essential food crop particularly in Sub-Saharan Africa. As breeders struggle to meet the rising demand for high-yielding and quality yam, hybridising underutilised wild species presents a promising solution. This study therefore investigated the potentials of hybridising two wild yam species, Dioscorea abyssinica and Dioscorea praehensilis known for their resilience and genetic potential as ancestors of the cultivated West African yam, Dioscorea rotundata, using hand-pollination method. Hybridity was assessed with eight subsets of Kompetitive allele-specific markers, and the progenies were evaluated morphologically using standard descriptors. Markers detected heterozygosity in 65 (92.9 %) of 70 progenies, confirming successful hybridisation. Significant (p < 0.05) variation was observed in growth and yield traits, with TDabp2101048, TDabp2101010, and TDabp2101068 excelling in stem length (348.91 cm), internode length (23.36 cm), and vigour (5.85) respectively. The highest tuber length (42.91 cm), tuber weight (1.14 kg) and number of tubers (4) were produced by TDabp2101052, TDabp2101046 and TDabp2101054, respectively. Progenies showed comparable traits to D. rotundata, indicating high genetic compatibility. These findings suggest putative potential for selecting superior genotypes, improving yam breeding programs through genetic diversity, enhancing crop resilience and productivity.